2020
DOI: 10.1111/cns.13472
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory microRNAs and vascular cognitive impairment and dementia

Abstract: Vascular cognitive impairment and dementia (VCID) is currently the second most common type of dementia just after Alzheimer's disease (AD). 1 In 2015, approximately 47.5 million people were affected by dementia, which is expected to increase to 75.6 million by 2030. The annual global social cost for VCID and vascular dementia (VaD) is $604 billion, accounting for 1.0% of the global gross domestic product. 2 Vascular cognitive impairment and dementia occurs when cerebral blood flow is compromised. It is a compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 140 publications
0
12
0
Order By: Relevance
“…Recently, specific microRNAs have been believed to be involved in the possible molecular mechanisms and signaling pathways of VCID pathophysiology. 76 Interestingly, previous study have demonstrated that Cx43-medicated GJIC can affect the angiogenesis of tumor via transferring microRNA from endothelial cells to tumor cells. 61 These valuable discoveries can provide another possible research direction for Cx43 in the VCID pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, specific microRNAs have been believed to be involved in the possible molecular mechanisms and signaling pathways of VCID pathophysiology. 76 Interestingly, previous study have demonstrated that Cx43-medicated GJIC can affect the angiogenesis of tumor via transferring microRNA from endothelial cells to tumor cells. 61 These valuable discoveries can provide another possible research direction for Cx43 in the VCID pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has suggested the diagnostic and therapeutic values of circulating non-coding RNAs in human diseases, and some excellent articles have reviewed microRNAs, long non-coding RNAs, or circular RNAs as promising non-invasive biomarkers for numerous CNS disorders. For example, microRNAs can be served as diagnostic and prognostic biomarkers of ischemic stroke [ 5 , 38 ], hemorrhagic stroke [ 39 ], traumatic brain injury (TBI) [ 40 ], spinal cord injury (SCI) [ 41 ], glioma [ 42 ], multiple sclerosis (MS) [ 43 ], Alzheimer’s disease (AD) [ 44 ], vascular cognitive impairment and dementia (VCID) [ 45 ], and others. LncRNAs have also been suggested as diagnostic and therapeutic biomarkers for stroke [ 46 ], TBI [ 47 ], SCI [ 48 ], glioma [ 49 ], MS [ 50 ], AD [ 51 ], and other diseases.…”
Section: Non-coding Rnas As Diagnostic and Prognostic Biomarkers For ...mentioning
confidence: 99%
“…The roles of miRNAs in the pathogenesis of vascular dementia have been widely studied, and further investigations of therapies that target miRNAs are considered important. 23 24 The results of the present study indicated that miR-322-5p was associated with the development of vascular dementia. As previously reported, miR-322 treatment rescues cell apoptosis and neural tube defect formation through silencing NADPH oxidase 4.…”
Section: Discussionmentioning
confidence: 54%